Service Use Preceding Opioid-Related Fatality - Olfson, Mark (Am J Psychiatry, 2017)
OBJECTIVE: To describe health service patterns before opioid-related death among non-elderly individuals in the Medicaid program focusing on decedents with and without past year diagnoses of non-cancer chronic pain. METHODS: We identified opioid-related decedents, ages 12 to 64 years in the Medicaid program, and characterized their clinical diagnoses, filled medication prescriptions, and non-fatal poisoning events during the 30 days and 12 months before death. The study group included 13,089 opioid-related deaths partitioned by presence or absence of chronic non-cancer pain diagnoses in the last year of life. RESULTS: Most decedents (61.5%) had received clinical diagnoses of chronic non-cancer pain conditions in the last year of life. As compared to fatalities without chronic pain diagnoses, those with these diagnoses were significantly more likely to have filled prescriptions for opioids (49.0% vs. 17.2%, p<.0001) and benzodiazepines (52.1% vs. 26.6%, p<.0001) during the last 30 days of life, while diagnoses of opioid use disorder during this period were uncommon in both groups (4.2% vs. 4.3%, p=0.87). The chronic pain group was also significantly more likely than the non-pain group to receive clinical diagnoses of drug use (40.8% vs. 22.1%, p<.0001), depression (29.6% vs. 13.0%, p<.0001) or anxiety (25.8% vs. 8.4%, p<.0001) disorders during the last year of life. CONCLUSIONS: Persons dying of opioid-related causes, particularly those who were diagnosed with chronic pain conditions, commonly received services related to drug use disorders and mental disorders in the last year of life, though opioid use disorder diagnoses near the time of death were rare.